Unraveling the universality of chemical fear communication: evidence from behavioral, genetic, and chemical analyses - de Groot, Jasper H.B.; Härtl, Tobias; Loos, Helene; Bachmann, Christin; Kontouli, Athanasia; Smeets, Monique A.M. (Chemical Senses, 2023)
Abundant evidence indicates that humans can communicate threat-related information to conspecifics through their body odors. However, prior research has been primarily conducted on Western (WEIRD) samples. In this study, we aimed to investigate whether threat-related information can be transmitted by individuals of East Asian descent who carry a single-nucleotide polymorphism (SNP) 538G → A in the ABCC11 gene, which significantly reduces (noticeable) body odor. To examine this, we recruited 18 self-identified male East Asian AA-homozygotes and 18 self-identified male Western individuals who were carriers of the functional G-allele. We collected samples of their fear-related and neutral body odors. Subsequently, we conducted a double-blind behavioral experiment in which we presented these samples to 69 self-identified female participants of Western Caucasian and East Asian backgrounds. The participants were asked to rate faces that were morphed between expressions of fear and disgust. Notably, despite the “odorless” phenotypical expression of the ABCC11-mutation in East Asians, their fear odor caused a perceptual fear bias in both East Asian and Caucasian receivers. This finding leaves open the possibility of universal fear chemosignaling. Additionally, we conducted exploratory chemical analysis to gain initial insights into the chemical composition of the body odors presented. In a subsequent pre-registered behavioral study (N = 33), we found that exposure to hexadecanoic acid, an abundant compound in the fear and neutral body odor samples, was sufficient to reproduce the observed behavioral effects. While exploratory, these findings provide insight into how specific chemical components can drive chemical fear communication.
CRIS-Team Scopus Importer:2024-12-16
Keywords: ABCC11 gene; analytical chemistry; chemical communication; emotion; olfaction; pre-registered